O Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Jovens e Adultos (PROEJA) na perspectiva de estudantes do IFMT - Duarte, Viviane Cristina de Oliveira (2020)
Considering the challenges and specificities that the National Program for the Integration of Professional Education with Basic Education in the Youth and Adult Education Modality (Proeja) presents to the school community, such as low enrollment rates and high dropout rates and based on the assumption that the social actors involved and subjects in the educational processes can provide data to help us understand this scenario, the present research aimed to understand, through narratives and simplified biographical research, how the students of the course Administration Technician - Proeja from the Federal Institute of Mato Grosso Campus Rondonópolis are perceived in the educational process in which they are inserted. It seeks to apprehend their perceptions about the school context and the asymmetric power relations in society (class, race/color, gender, age) that cross their school and life trajectories. The locus for conducting the field research was the Federal Institute of Mato Grosso Câmpus Rondonópolis and the participants were students of the Technical Course in Administration - Proeja. As specialized literature, we rely on the studies of Paulo Freire and Miguel Arroyo on Youth and Adult Education (EJA) and Proeja. We also supported, as an input, the theoretical and methodological framework of John B. Thompson, on the structural conception of culture and the methodology of Depth Hermeneutics (HP). From the analysis of the students' narratives, collected through conversation circles, and from the data from the simplified biographical questionnaire, we were able to apprehend that asymmetries of gender, class and race/color contributed significantly to the exclusion of participants from the regular education research and that the return to studies is marked by the need for social insertion, the search for quality education and the possibility of being able to enter a public university. Therefore, technological and professional education is not the central motivation for this audience. We were also able to apprehend that the singularities of the Proeja public have not been considered in the IFMT curricula, regulations and student assistance policies. These are workers, mothers, fathers, family providers, who need to find welcoming times, curricula and spaces in this return to school, which consider the diversity of the individual and collective itineraries of these students.